PRAGMATIC MARKERS AS CONTEXT BOUNDARIES IN INDONESIAN HUMOROUS TALK SHOWS DISCOURSE (Italiano LinguaDue, 2023)
In building a successful conversation, speakers are bound to bring proper linguistic devices to keep the hearer’s understanding in processing the appropriate inferences beyond the utterances. This study aims to investigate the function of pragmatic markers in creating context boundaries in the cognitive process (Kecskes & Zang, 2014). Pragmatic markers are believed not only to serve the coherence of the discourse but also to signal the speaker’s cognitive process (Blakemore, 1987:144). In this case, pragmatic markers function to guide the hearers in picking up the interlocutor’s knowledge (Nordenstam, 1992) in creating humor. The corpus data used in this study is collected from manual transcription (with annotation) of 10 chosen humorous talk show videos in Indonesian. The investigation focuses on pragmatic marker lho used in Indonesian humorous discourse which suggests that the conversational humor is creatively created with the high frequency of the communicating speaker’s knowledge to create incongruity to fill the conversation with unexpected or even unrealistic ideas that people never imagine. As a result, pragmatic markers lho play essential roles in guiding the hearer to the intended context so that they can choose the appropriate inferences based on the shared knowledge that leads them to grab the humorous sense of the utterances. Marcatori pragmatici come confini del contesto nel discorso dei talk show umoristici indonesianiNella costruzione di una conversazione di successo, i parlanti sono tenuti a mettere in atto dispositivi linguistici adeguati per mantenere la comprensione dell’uditore nell’elaborazione delle inferenze appropriate al di là degli enunciati. Questo studio si propone di indagare la funzione dei marcatori pragmatici nel creare confini contestuali nel processo cognitivo (Kecskes, Zang, 2014). Si ritiene che i marcatori pragmatici non servano solo alla coerenza del discorso, ma anche a segnalare il processo cognitivo del parlante (Blakemore, 1987). In questo caso, i marcatori pragmatici hanno la funzione di guidare gli uditori a cogliere le conoscenze dell’interlocutore (Nordenstam, 1992) nel creare umorismo. I dati del corpus utilizzati in questo studio sono tratti dalla trascrizione manuale (con annotazione) di 10 video di talk show umoristici in indonesiano. L’indagine si concentra sul marcatore pragmatico lho utilizzato nel discorso umoristico indonesiano, che suggerisce che l’umorismo conversazionale è creato in modo creativo con l’alta frequenza delle conoscenze del parlante per creare incongruenza e riempire la conversazione con idee inaspettate o addirittura irrealistiche che le persone non avrebbero mai immaginato. Di conseguenza, i marcatori pragmatici lho svolgono un ruolo essenziale nel guidare l’uditore verso il contesto previsto, in modo che possa scegliere le inferenze appropriate in base alla conoscenza condivisa che lo porta a cogliere il senso umoristico degli enunciati.